A highly efficient 3D micromixer using soft PDMS bonding - Cha, Junghun; Kim, Jinseok; Ryu, Suk-Kyu; Park, Jungyul; Jeong, Yongwon; Park, Sewan; Park, Sukho; Kim, Hyeon Cheol; Chun, Kukjin (IOP PUBLISHING LTD, 2006)
This paper presents a novel highly efficient passive micromixer that employs diffusion for micromixing. Since conventional fabrication methods cannot form precise aligned microchannels, the realization of a complex 3D micromixer has been difficult. Here, we report a novel micromixer, named a chessboard mixer. In addition, a new polydimethylsiloxane ( PDMS) bonding method was developed to produce the proposed mixer. The new PDMS bonding technique requires PDMS-to-PDMS bonding and the moldable flexibility of partially cured PDMS to form the structure. Accordingly, a two-step curing process was used to solve these problems. Adhesion control was also considered when forming the PDMS membranes. Complex 3D microchannels in the micromixer were aligned within 1 m using the proposed new bonding method. The presented micromixer could increase the mixing effect by expanding interfaces between mixing fluids. Thus, this mixer makes it possible to mix within a shorter distance than other pre-existing micromixers do. A simulation using computational fluid dynamics (CFD)-ACE software showed a highly efficient performance, and an experiment involving the mixing of NaOH and phenolphthalein confirmed the rapid mixing performance (< 1400 mu m).
Keywords: TOTAL ANALYSIS SYSTEMS; MICROFLUIDIC MIXER